Complication rates of direct puncture and pull-through techniques for percutaneous endoscopic gastrostomy: Results from a large multicenter cohort - Schuhmacher, Leonie; Bojarski, Christian; Reich, Victoria; Adler, Andreas; Veltzke-Schlieker, Winfried; Jürgensen, Christian; Wiedenmann, Bertran; Siegmund, Britta; Branchi, Federika; Buchkremer, Julianne; Hornoff, Steffen; Hartmann, Dirk; Treese, Christoph (Endoscopy International Open, 2022)
Background and study aims Two different techniques for percutaneous endoscopic gastrostomy (PEG) have been developed: classical pull-through and direct puncture techniques. This study compared the complication rate for both techniques in a large retrospective patient cohort.Patients and methods Clinical data from patients who received a PEG in four high-volume centers for endoscopy were included retrospectively between January 2016 and December 2018. Patient characteristics and complication rates were correlated in univariate and multivariate analyses.Results Data from 1014 patients undergoing a PEG insertion by the pull-through technique were compared to 183 patients for whom the direct puncture technique was used. The direct puncture technique was associated with a 50 % reduction in minor and 85.7 % reduction in major complications when compared to the pull-through technique. Multivariate analysis of these data revealed an odds ratio of 0.067 (0.02–0.226; P < 0.001) for major complications in the direct puncture group.Conclusions Compared to the pull-through technique, the direct puncture technique resulted in a significant reduction in complications. Despite the retrospective design of this study, these results suggest that the direct puncture technique may be preferable to improve patient safety.